Cellulose nanocrystals from grape pomace and their use for the development of starch-based nanocomposite films - Coelho, C. C. S. (2020)
Nanocomposite films prepared from starch (ST) in the presence of cellulose nanocrystals (CNCs) was performed using grape pomace as raw material. CNCs were obtained by acid hydrolysis and added to filmogenic solutions (1, 2, 5, 10 and 15 g/100 g of ST). Cellulose, CNCs and Nanocomposites were characterized. Amorphous non-cellulosic materials were removed from the grape pomace presented values for CrI 64% and 71% and yield 12 and 70% in Cellulose and CNCs, respectively. Nanocomposites showed smaller permeability and the addition of 5 to 15% CNCs formed more opaque films and had improved tensile strength and Youngs modulus. The addition of CNCs from 5 to 15% proved to be effective in improving mechanical properties and decreasing water vapor permeability, important characteristics in food packaging materials. This study provided an effective method to obtain CNCs from the agroindustrial waste and open the way to produce high-value starch based nanocomposites.